A Pragmatist Framework for Disagreeing Deeply - Forero-Mora, José Andrés; Frápolli, María José (Informal Logic)

(untitled) (Informal Logic, 2026)
In this paper, we argue that much of the recent discussion on deep disagreement is grounded in a semantic framework that fails to capture how the concept actually works. It overlooks a key point that we aim to emphasize: attributing depth to a disagreement is, at its core, an evaluative act. Drawing on a pragmatist perspective, we propose a more refined framework that reveals how certain terms serve to express—or make explicit—the speaker’s attitudes and intentions in the act of speaking. We argue that this is exactly what occurs when depth is attributed to a disagreement.